Effect of Chiranjeevi Yojana on Institutional Deliveries and Neonatal and Maternal Outcomes in Gujarat, India : A Difference-in-Differences Analysis - Mohanan, Manoj; Bauhoff, Sebastian; La Forgia, Gerard; Singer Babiarz, Kimberly; Singh, Kultar; Miller, Grant (World Health Organization, 2015)
A household survey (n = 5597 households) was conducted in Gujarat to collect retrospective data on births within the preceding 5 years. In an observational study using a difference-in-differences design, the relationship between the Chiranjeevi Yojana program and the probability of delivery in health-care institutions, the probability of obstetric complications and mean household expenditure for deliveries was subsequently examined. In multivariate regressions, individual and household characteristics as well as district and year fixed effects were controlled for. Data from the most recent District Level Household and Facility Survey (DLHS-3) wave conducted in Gujarat (n = 6484 households) were used in parallel analyses.